2-Pentanone Production from Hexanoic Acid by Penicillium roqueforti from Blue Cheese: Is This the Pathway Used in Humans? - Valerie Walker; Graham A. Mills (The Scientific World Journal)
Production of 2-pentanone, a methylketone, is increased in fasting ketotic humans. Its origin is unknown. We hypothesised that it is formed via β-oxidation of hexanoic acid by the peroxisomal pathway proposed for methylketone-producing fungi and yeasts. We used Penicillium roqueforti cultured on fat (margarine) to investigate 2-pentanone production. Headspace gas of incubates of the mould with a range of substrates was analysed using solid-phase microextraction with gas chromatography-mass spectrometry. Consistent with the proposed pathway, 2-pentanone was formed from hexanoic acid, hexanoyl-CoA, hexanoylcarnitine, and ethyl-3-oxohexanoic acid but not from ethylhexanoic, 2-ethylhexanoic, octanoic, or myristic acids, octanoylcarnitine, or pentane. However, the products from deuterated (D) hexanoic-D11 acid and hexanoic-2, 2-D2 acid were 9D- and 2D-2-pentanone, respectively, and not 8D- and 1D-2-pentanone as predicted. When incubated under 18O2/14N2, there was only a very small enrichment of [16O2]- with [18O2]-containing 2-pentanone. These are new observations. They could be explained if hydrogen ions removed from hexanoyl-CoA by acyl-CoA oxidase at the commencement of β-oxidation were cycled through hydrogen peroxide and reentered the pathway through hydration of hexenoyl-CoA. This would protect other proteins from oxidative damage. Formation of 2-pentanone through a β-oxidation cycle similar to Penicillium roqueforti would be consistent with observations in humans.